Diversity and evolution of anuran trypanosomes: insights from the study of European species - Viktoria V. Spodareva; Anastasiia Grybchuk‐Ieremenko; Alexander Losev; Jan Votýpka; Julius Lukeš; Vyacheslav Yurchenko; Alexei Yu. Kostygov (2018)
Amphibian trypanosomes were the first ever described trypanosomatids. Nevertheless, their taxonomy remains entangled because of pleomorphism and high prevalence of mixed infections. Despite the fact that the first species in this group were described in Europe, virtually none of the trypanosomes from European anurans was analyzed using modern molecular methods. In this study, we explored the diversity and phylogeny of trypanosomes in true frogs from Europe using light microscopy and molecular methods. A comparison of observed morphotypes with previous descriptions allowed us to reliably identify three Trypanosoma spp., whereas the remaining two strains were considered to represent novel taxa. In all cases, more than one morphotype per blood sample was observed, indicating mixed infections. One hundred and thirty obtained 18S rRNA gene sequences were unambiguously subdivided into five groups, correspondent to the previously recognized or novel taxa of anuran trypanosomes. In this work we studied European frog trypanosomes. Even with a relatively moderate number of isolates, we were able to find not only three well-known species, but also two apparently new ones. We revealed that previous assignments of multiple isolates from distant geographical localities to one species based on superficial resemblance were unjustified. Our work also demonstrated a high prevalence of mixed trypanosome infections in frogs and proposed a plausible scenario of evolution of the genus Trypanosoma.